Analytical Solution For The First Order Reversible Reaction System Through Flow Graph Theory Approach - Hasan, Nurul Amira Syakilla (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
An analytical solution for the first order reversible reaction was derived using the flow theory approach. Reversible reactions are the chemical reactions that results in an equilibrium mixture of reactants and products. The usage of flow graph theory was simpler and more direct in solving the exact solution which then will eliminate the classical integration, Laplace transform and eigenvalue methods. The flow graph was based the image of reaction stoichiometry and the ratio of consumption and formation flow graph was used to find an analytical solution of the reaction system. In this report, the analytical solutions for the two species and three species reaction system were derived and verified with the numerical integration of the governing ordinary differential equations by using MATLAB software.